Two‐Step Direct Transesterification as a Rapid Method for the Analysis of Fatty Acids in Microalgae Biomass. Issue 5 (27th March 2019) - Safafar, Hamed; Ljubic, Anita; Møller, Per; Jacobsen, Charlotte
Abstract : A rapid and routine direct transesterification (DT) method for the evaluation of the relative fatty acid composition of microalgae biomass is presented in this paper. The method is optimized on Lake Superior Fish Tissue (SRM 1946), as standard reference material and then the proposed DT procedure is tested on various microalgae species, and the results are compared to a validated microwave assisted esterification (MAE) as a reference ( R 2  = 0.99). Total DT time is very fast (14 min), while the fatty acid compositions are virtually identical to those prepared by MAE for various species of microalgae as well as fish and krill biomasses. Practical Applications : Microalgae are known as a sustainable source of bioactive compounds such as fatty acids, and their implementation is growing. Application of microalgae biomass as a source of fatty acids requires fast and reliable methods of analysis of fatty acids. The DT method developed in this study can be used as a powerful tool for the monitoring of the variations in fatty acid composition during the cultivation, processing, formulation, and storage. The fatty acid composition of microalgae has been proven as a potential tool for the identification of microalgal taxa. Application of fatty acid composition as a fingerprinting tool requires fast, reliable, and precise methods. A rapid and routine direct transesterification method for the evaluation of the fatty acid composition of microalgae biomass is presented in this paper. The transesterification is being done in two steps as sonication assisting base‐catalyzed methanolysis followed by BF3 methylation reactions. Heating in boiling water bath for 2 min is required at both steps to improve the reactions. Abstract : The fatty acid composition of microalgae has been proven as a potential tool for the identification of microalgal taxa. Application of fatty acid composition as a fingerprinting tool requires fast, reliable, and precise methods. A rapid and routine direct transesterification method for the evaluation of the fatty acid composition of microalgae biomass is presented in this paper. The transesterification is being done in two steps as sonication assisting base‐catalyzed methanolysis followed by BF3 methylation reactions. Heating in boiling water bath for 2 min is required at both steps to improve the reactions.